Cutaneous manifestations associated with unknown HIV infection: a case report - Iacovelli, Paolo; Pigliacelli, Flavia; Mariano, Maria; Cameli, Norma; Giglio, Amalia; Pacifico, Alessia; Gianserra, Laura; Latini, Alessandra; Stingone, Christof (Dermatology Reports, 2025)
Cutaneous manifestations are extremely common in people living with human immunodeficiency virus (PLHIV), and sometimes, these manifestations can help with the diagnosis. In the advanced stages of the infection, the impairment of the immune system can increase susceptibility to cutaneous infections. We present the case of a patient affected by an unknown advanced human immunodeficiency virus (HIV) infection whose diagnosis was made through skin manifestations.